2016
DOI: 10.1080/19490976.2016.1216747
|View full text |Cite
|
Sign up to set email alerts
|

Partial recovery of microbiomes after antibiotic treatment

Abstract: Antibiotics profoundly affect the gut microbiome and modulate microbial communities. We recently observed that antimicrobial drugs also impact the abundance and distribution of antibiotic resistance genes. In this addendum, we reanalyze our »1 trillion nucleotide shotgun metagenomic dataset to quantify comprehensive genomic differences at the sequence level before and after antibiotic treatment. We show that 7 day exposure to cefprozil leads to a statistically significant loss of metagenome sequences. Recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 20 publications
1
32
2
Order By: Relevance
“…These observations were not surprising. Microbiota disruption has been documented in healthy dogs and humans receiving PO antibiotics . Alteration of gut microbiota is not necessarily detrimental to the host, and different microbiota compositions can be compatible with health .…”
Section: Discussionmentioning
confidence: 99%
“…These observations were not surprising. Microbiota disruption has been documented in healthy dogs and humans receiving PO antibiotics . Alteration of gut microbiota is not necessarily detrimental to the host, and different microbiota compositions can be compatible with health .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Corbeil et al showed that a 7-day exposure to cefprozil led to a loss of metagenome-defined species. Although recovery of the gut microbiota occurred after 3 months from ATB discontinuation, important and lasting changes in the genomic content were seen, especially in participants with a low baseline gut microbiota diversity [48].…”
Section: Atb-related Dysbiosis and Impact Of Atb On Efficacy Of Immunmentioning
confidence: 98%
“…Once treatment ends, a recovery of the composition of the microbiome is observed after some time. However, recent information indicates that, although the structure of the taxonomic groups is similar three months after treatment to the one observed before antibiotic application 13 , the specific clones that re-colonize the gut are not the same as those before treatment. This means that while the overall structure of the population remains, the overall genomic content largely varies 13 .…”
Section: Multi-hierarchical Antibiotic Selection Of Bacterial Populatmentioning
confidence: 90%
“…However, recent information indicates that, although the structure of the taxonomic groups is similar three months after treatment to the one observed before antibiotic application 13 , the specific clones that re-colonize the gut are not the same as those before treatment. This means that while the overall structure of the population remains, the overall genomic content largely varies 13 . These results indicate that the effect of antibiotics on the structure of the populations will remain long after they disappear from the polluted habitat.…”
Section: Multi-hierarchical Antibiotic Selection Of Bacterial Populatmentioning
confidence: 90%